ULCERS OF PRESSURE IN PATIENTS OF INTENSIVE THERAPY UNIT: INCIDENCE AND ASSOCIATION OF RISK FACTORS. (Fiep Bulletin - online, 2015)
This is a descriptive study, with longitudinal delineation, conducted in two ICUs of private hospital in Natal/RN, with 40 admitted patients, with objectives try to identify the PU incidence, according to sex, age, period in hospital, disgnostic hypothesis and localization of PU and to verify the existence of association between risk factors in the PU occurrence. The data collection was conducted in three shifts by a structuralizaed form of comment and physical examination of the skin of the patients. The highest occurrence of PU was in male sex (70%, p = 0,0267 and OR = 4,3 times) in relation to the female one (30%); 60,0% had presented from 1 to 2 PUs after 7 days of admittance in the ICUs, the disgnostic hypothesis predominant  had been the respiratory illnesses (42,3%)  and the most frequent localizations of PU had been to the sacral region (40,0%) and heels (36,0%). 25 pressure ulcers satege 1 had been diagnosised in 50,0% of the followed patients, with incidence of 50% in the two ICUs.
Keywords: Pressure ulcer; Intensive care unit; Patient.